Parents' Sexual Orientation and Children's Development. (14th November 2016) - Patterson, Charlotte J.
Abstract: What if any influence does parents' sexual orientation have on children's development? Research suggests that, contrary to concerns voiced by many observers, parents' sexual orientation has little if any direct impact on children's development. Even so, some distinctive qualities of experiences in families of lesbian and gay parents have been noted, and their implications are not fully understood. Moreover, research on individual differences among families headed by lesbian mothers and gay fathers, and their possible impact on children, is still in its early phases. In this article, I provide an overview of research in this area and offer suggestions for further studies.